Экспериментальные исследования горения традиционных зарядов в условиях сопловой бомбы - Кодякова, Анастасия Денисовна (Перспективы развития фундаментальных наук. Т. 1 : сборник научных трудов XX Международной конференции студентов, аспирантов и молодых ученых, 25-28 апреля 2023 г.)
One of the main tasks of the internal ballistics of barrel systems is to increase the muzzle velocity of the missile element. One of the promising directions is the use of new high-density fuels as an attached charge. To use these fuels in desktop systems, knowledge about the combustion of the studied fuels is required. It is possible to obtain these regularities from an experiment conducted under the conditions of a nozzle bomb. This paper presents technical solutions that make it possible to study various types of high-density fuels under the conditions of a nozzle bomb. Various options for realizing the maximum pressure in the combustion chamber of a nozzle bomb are considered, due to the use of various methods of "opening" the nozzle block.